Social scaffolding applying the lessons of contemporary social science to health and healthcare - Bailey, Susan; Bhui, Kamaldeep S.; Haslam, Catherine; Haslam, S. Alexander; Kemp, Verity; Williams, Richard 1949 February 5- (Cambridge University Press, 2019)
Using current societal dilemmas, this book explores how social factors and social identity influence our health and recovery from illness. It includes recent research to present practitioners, researchers, policymakers and students of many disciplines with the material to support them in better harnessing current knowledge of the impact of social factors on health. The contents will influence collaborative working across policy, disciplinary and practice boundaries to design and deliver healthcare services. The book identifies the importance of social connectedness, social support, agency and self and group efficacy in people's health, longevity and resilience after adversity. Core perspectives include the social identity approach and a values framework for taking public health ethics into decision-making, both of which emphasise valuing people and co-productive relationships. Advocating better targeted mental health promotion and integrated interventions, this book strongly argues for a greater emphasis on social factors in evidence-based and cost-effective practice.